Hedley bull on arms control - Bull, Hedley (London, 1987)
This selection of the most important articles and essays by the late Hedley Bull on arms control theory includes his early seminal theoretical work, commentary on specific arms-control agreements, and more recent thinking on the relationship between arms control problems and broader issues of international relations. It will be valuable not only to the specialist in the field but also to anyone with an interest in the most complex international problems of the modern world.
Keywords: Arms control